Mongolia : Heating Stove Market Trends in Poor, Peri-Urban Ger Areas of Ulaanbaatar and Selected Markets Outside Ulaanbaatar - World Bank (Washington, DC, 2014)
Ulaanbaatar, Mongolia is the coldest capital of the world and remains one of its most polluted. Coal and wood burning for heating are essential for survival but contribute about 60 percent of the fine particulate (PM2.5) concentrations in the city. These levels of exposure are very harmful to health and exceed World Health Organization (WHO) standards many-fold. The heating appliances causing the pollution are both traditional stoves that have been used for generations and, increasingly, coal fired stove furnaces used by wealthier households. The overwhelming majority of households in the ger areas (informal settlements surrounding the city), however, are poor, and the population continues to grow as job prospects in Ulaanbaatar attract more migrants. The World Bank estimates that a reduction of 80 percent of emissions from ger area heating could achieve a 48 percent reduction in population weighted exposure to PM2.5. To achieve this, poor households need to be convinced to permanently switch to less polluting heating solutions, an effort that will require a multi-year, coordinated set of policies and programs. This study takes stock of recent developments and provides market information on affordability, attitudes, fuel consumption, and other market information for stoves and fuels inside and outside Ulaanbaatar. It provides insights for solutions to the important challenges that remain to achieve a sustainable market transformation to low-emission stoves.